Worldviews in World Politics - Peter J. Katzenstein (Uncertainty and Its Discontents: Worldviews in World Politics, 2022)
This chapter discusses the concept of worldview; relates it to paradigms and substantialist and relational reasoning; maps Newtonianism and Post-Newtonianism (quantum mechanics) and humanism and hyper-humanism (scientific cosmology) as two different dimensions structuring implicit worldviews; specifies four analytical perspectives on world politics; and concludes briefly with two illustrative applications.
Keywords: 320